Development and usage of protein microarrays for the quantitative measurement of Panton-Valentine leukocidin - Stieber, B.; Monecke, S.; Mϋller, E.; Baier, V.; Coombs, Geoffrey; Ehricht, R. (Elsevier, 2013)
Staphylococcus aureus is a human pathogen that can harbour several genes encoding exotoxins including leukocidins. A clinically most relevant factor is Panton-Valentine leukocidin (PVL) because of its association with chronic, recurrent or severe skin and soft tissue infections. In this study an antibody array was designed and used to obtain an overview about the in vitro PVL expression levels of 266 clinical isolates of MRSA as well as of MSSA belonging to a wide variety of clonal complexes. For that purpose, a novel precipitation based method was used. Unknown PVL concentrations were determined by mapping the signal intensities for spotted monoclonal antibodies to calibration curves that resulted from experiments with known concentrations of recombinant LukF-PV. In most cases, isolates belonging to one clonal complex (CC) showed similar PVL expressions. However, there were also CCs with widely varying PVL concentrations. First analyses, based on in vitro PVL measurements, showed low PVL concentrations in isolates from severe and fatal conditions that are not associated with PVL, such as sepsis, while isolates from skin and soft tissue infections yielded higher concentrations. Agr-group I and IV isolates generally produced more PVL than isolates from agr-groups II and III. The few isolates harbouring the gene encoding toxic shock syndrome toxin (tst1) were particularly low level PVL producers. However, these issues warrant further studies. The method described herein allows rapid quantification of expressed proteins such as PVL in collections of clinical isolates in order to correlate with clinical or genotypic data with a potential for further parallelisation